PERSONAL HOLDINGS OF THE POPULATION OF THE ZAKARPATA REGION (80-90s of the ХХ th century) - Жулканич, Неля (SWorldJournal, 2024)
The article examines the aspects of the development of the personal auxiliary economy of the population in general and the Transcarpathian region, in particular. The agrarian policy of the state regarding the operation of the analyzed farms is considered;